Left atrium remodeling after catheter ablation of atrial fibrillation - Chango Azanza, Diego Xavier (2023)
Atrial fibrillation (AF) is the most common cardiac arrhythmia. It has a high association with cardiovascular embolic events and heart failure. Structural and functional changes are a fundamental part of the pathophysiological process, leading to left atrial myopathy and progressive left ventricular dysfunction that modifies the prognosis of patients. We present the case of a 75-year-old patient with symptomatic paroxysmal AF with good functional class who was referred for pulmonary vein ablation after antiarrhythmic therapy failure. The initial echocardiogram showed preserved biventricular systolic function, mild diastolic dysfunction, and normal left atrium (LA) volumes. However, functional LA impairment was observed with decreased reservoir phase strain. Pulmonary vein isolation was successfully performed without evidence of new arrhythmic events, in addition to improvement in LA reservoir strain, left ventricular (LV) global longitudinal strain, and myocardial work index at three months follow-up. The patient has remained asymptomatic and is under clinical follow-up. LA and LV strain as new advanced echocardiography techniques is useful in the assessment of reverse remodeling of atrial myopathy and LV structural assessment.